Estaurosporinas de Eudistoma vannamei : química e bioatividade - Jimenez, Paula Christine (2009)
Eudistoma vannamei Millar, 1977 is an endemic tunicate from the northeastern Brazilian coast, widely distributed over the rocky beaches of Ceará State. Previously, the crude extract showed an interesting bioactivity profile. Bioassay-guided fractionation yielded a highly cytotoxic 1:1 mixture identified as two novel staurosporine derivatives, 2-hydroxy-7-oxostaurosporine (I) and 3-hydroxy-7-oxostaurosporine (II). IC50 for I/II and staurosporine (STP) were obtained after 72h incubation with various tumor cell lines using the MTT assay and in normal human lymphocytes, by the AlamarBlue assay, where I/II outperformed STP in a 7-fold average. On normal cells, I/II showed to be equally effective as STP and, thus, showed a 25-fold average selectivity towards tumor cells. A kinetic analysis on cell cycle progression, activation of DNA damage and repair pathways and apoptosis induction of HL-60 cells (leukemia), was carried out with 40 or 80ng/mL I/II and accessed by flow cytometry and western blotting. Cell cycle studies indicated that I/II induces a G2-M arrest (at 40ng/mL, 45, 63 and 94% of arrested cells after 24, 48 and 72h treatment, respectively, against 9, 10 and 13% for the non-treated culture). Moreover, 24h-G2/M arrest is sustained and irreversible following removal of stimuli. STP induces 83% G2/M arrest at 200ng/mL after 24h incubation, whilst longer incubation periods provoke a substantial increase in polyploidy. Expression-rate of cell cycle related proteins (Cdk1, Cdk2, cyclin A and cyclin B1) paired with morphological observation of 40ng/mL I/II-treated H/E-stained cells placed on glass slides suggest that arrest is actually occurring at the G2 phase. G2 arrest is merely seen in 80ng/mL I/II-treated cells, while apoptotic features were quite evident. Double-strand breaks evaluated by the neutral comet assay indicates only low scored DNA damage against 24, 48 or 72h 40ng/mL I/II treated cells. However, 80ng/mL I/II-treated cells exhibited higher scored damage. DNA damage proteins (ATM and H2A.X) were expressed in a time- and concentration-dependent manner; while, cycle arrest and repair markers (Chk1, Cdc25C, BRCA1) were activated mostly on 40ng/mL I/II-treated cells. Conversely, PS externalization and activation of effector caspases 3 and 7 and PARP were highly blotted mostly for 80ng/mL I/II-treated cells. I/II induced a clear cytostatic effect on HL-60 cells at the lower concentration, distinguished by persistent cell cycle arrest and low DNA damage; and an objective cytotoxic effect at the higher concentration, motivated by extensive DNA damage and induction of apoptosis.